The Mediating Role of Employee Engagement in the Relationship between Digital Transformational Leadership and Organizational Agility in Indonesian Manufacturing SMEs - Dolly Putra Parlindungan; Widya Pratiwi; Ariyanto Masnun; Obing Zaid Sobir; Nirmala Haty Harahap; Melati Sukma Dewi Lasubang (PT Inovasi Pratama Internasional, 2026)
This study examines the mediating role of employee engagement in the relationship between digital transformational leadership and organizational agility within manufacturing SMEs in North Sumatra. The digital era demands that organizations, particularly small and medium enterprises in emerging economies, exhibit agility to remain competitive. While digital transformational leadership is recognized as a driver of such agility, the specific mechanisms facilitating this relationship require further investigation, especially in contexts like Indonesia where employee engagement may be pivotal. Grounded in the Resource-Based View, this research employs a quantitative approach. Data were collected via structured questionnaires from 180 respondents across 60 manufacturing SMEs in North Sumatra, including owners, managers, and supervisors. The conceptual model was tested using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings reveal that digital transformational leadership significantly and positively influences organizational agility (β = 0.312, p < 0.001) and employee engagement (β = 0.623, p < 0.001). Employee engagement also significantly affects organizational agility (β = 0.498, p < 0.001). Furthermore, employee engagement mediates the relationship between digital transformational leadership and organizational agility (β = 0.310, p < 0.001). This study contributes to the literature by clarifying the underlying role of employee engagement in translating digital leadership into organizational responsiveness. For practitioners, the findings provide actionable insights for SME leaders in Indonesia on how to strategically foster employee engagement to maximize the benefits of digital transformation, thereby enhancing organizational agility and long-term sustainability.